2020
DOI: 10.1155/2020/7534693
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers and Berberine: A Possible Dual Approach to Contrast Neuroblastoma Growth and Progression

Abstract: The use of nutraceuticals during cancer treatment is a long-lasting debate. Berberine (BBR) is an isoquinoline quaternary alkaloid extracted from a variety of medicinal plants. BBR has been shown to have therapeutic effects in different pathologies, particularly in cancer, where it affects pathways involved in tumor progression. In neuroblastoma, the most common extracranial childhood solid tumor, BBR, reduces tumor growth by regulating both stemness and differentiation features and by inducing apoptosis. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…Berberine treatment produced the induction of neuronal cell differentiation, attenuated cancer stemness markers, and potentiated G0/G1 cell cycle arrest in neuro2a (N2a) neuroblastoma cells [216]. Concurrent inhibition of β-adrenergic signaling pathways with a β-blocker and inhibition of MAO-A with berberine 6 produced attenuation of tumor growth and an increase in differentiation of cells [217].…”
Section: Natural Mao Inhibitors In Neuroblastomamentioning
confidence: 99%
“…Berberine treatment produced the induction of neuronal cell differentiation, attenuated cancer stemness markers, and potentiated G0/G1 cell cycle arrest in neuro2a (N2a) neuroblastoma cells [216]. Concurrent inhibition of β-adrenergic signaling pathways with a β-blocker and inhibition of MAO-A with berberine 6 produced attenuation of tumor growth and an increase in differentiation of cells [217].…”
Section: Natural Mao Inhibitors In Neuroblastomamentioning
confidence: 99%
“…Around the same time, inhibiting the adrenergic signal slows neuroblastoma development and increases cell differentiation. Calvani et al [ 108 ] have summarized the potential benefits of BBR in inhibiting tumor growth and development in different types of cancer, especially neuroblastoma [ 108 ], BBR (6.25–200 μmol/L, 6–48 h) impaired cell viability and proliferation of U87 and U251 human glioblastoma cell lines in BALB/c nude mice (IC 50 of 42 and 32 μmol/L, respectively). BBR (50 μmol/L) prevented HUVEC cell migration in the transwell assay by 67.50 ± 8.14% and the Matrigel assay by 73.00 ± 1.12% [ 109 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…During DM there is a relationship between inflammation and oxidative stress which leads to the creation of proinflammatory cytokines such as IL-6 and TNF-α [104]. It was reported that BER counteracts some inflammatory processes where it attenuates NADPH oxidase (NOX) that is responsible for reactive oxygen species (ROS) generation, thereby decreasing AGEs and increasing endothelial function in DM [105]. BER displayed a tendency to ameliorate the inflammation resulting from DM via various pathways, e.g., suppression of phosphorylated Toll-like receptor (TLR) and IkB kinase-β (IKK-β) that is responsible for NF-κB activation; thus, BER interferes with the serine phosphorylation of IRS and diminishes insulin resistance [106].…”
Section: Berberine (Ber)mentioning
confidence: 99%